Arrest in the Progression of Type 1 Diabetes at the Mid-Stage of Insulitic Autoimmunity Using an Autoantigen-Decorated All-trans Retinoic Acid and Transforming Growth Factor Beta-1 Single Microparticle Formulation - Phillips, Brett E.; Garciafigueroa, Yesica; Engman, Carl; Liu, Wen; Wang, Yiwei; Lakomy, Robert J.; Meng, Wilson S.; Trucco, Massimo; Giannoukakis, Nick (Frontiers in Immunology, 2021)
Type 1 diabetes (T1D) is a disorder of impaired glucoregulation due to lymphocyte-driven pancreatic autoimmunity. Mobilizing dendritic cells (DC) in vivo to acquire tolerogenic activity is an attractive therapeutic approach as it results in multiple and overlapping immunosuppressive mechanisms. Delivery of agents that can achieve this, in the form of micro/nanoparticles, has successfully prevented a number of autoimmune conditions in vivo. Most of these formulations, however, do not establish multiple layers of immunoregulation. all-trans retinoic acid (RA) together with transforming growth factor beta 1 (TGFβ1), in contrast, has been shown to promote such mechanisms. When delivered in separate nanoparticle vehicles, they successfully prevent the progression of early-onset T1D autoimmunity in vivo. Herein, we show that the approach can be simplified into a single microparticle formulation of RA+TGFβ1 with surface decoration with the T1D-relevant insulin autoantigen. We show that the onset of hyperglycemia is prevented when administered into non-obese diabetic mice that are at the mid-stage of active islet-selective autoimmunity. Paradoxically, the preventive effects do not seem to be mediated by increased numbers of regulatory T-lymphocytes inside the pancreatic lymph nodes (PLN). Instead, we observed a mild increase in the frequency of IL-10-producing regulatory B-lymphocytes inside the mesenteric lymph nodes. These data suggest additional and potentially-novel mechanisms that RA and TGFβ1 could be modulating to prevent progression of mid-stage autoimmunity to overt T1D. Our data further strengthen the rationale to develop RA+TGFβ1-based micro/nanoparticle “vaccines” as possible treatments of pre-symptomatic and new-onset T1D autoimmunity.